2010
DOI: 10.1021/jz101202a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Gold Nanoshells: Stepwise Changing of Magnetism through Stepwise Biofunctionalization

Abstract: We report step-wise changing of magnetic behavior of iron oxide core gold shell nanoparticles from super paramagnetic to permanent magnetism at room temperature, on step-wise biofunctionalization with leutenizing hormone and releasing hormone (LHRH) through cysteamine linker. The observed permanent magnetism at room temperature in LHRH-capped gold nanoshells provides opportunities to extend fundamental investigations of permanent magnetism to other novel nanostructures and biofunctionalized nano gold architect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…[ 6 ] We have also recently demonstrated ferromagnetism in peptide-capped gold nanoshells ( ∼ 0.5 nm thick) and the possibility to modulate their magnetic behavior by step-wise functionalization of stabilizing ligands. [ 7 ] It is generally observed that ferromagnetism at room temperature in gold nanoparticles prevails in thiol-stabilized Au nanoparticles. [ 8 ] The crucial electronic event involved on the onset of magnetization in capped gold nanoparticles is a spin symmetry breaking associated with the 5 d and 6 s electrons of the Au atoms involved in the chemical bond with the ligands, which in turn modifi es the relative spin densities at the Fermi energy thus creating a non-zero magnetic moment and a corresponding magnetization.…”
mentioning
confidence: 99%
“…[ 6 ] We have also recently demonstrated ferromagnetism in peptide-capped gold nanoshells ( ∼ 0.5 nm thick) and the possibility to modulate their magnetic behavior by step-wise functionalization of stabilizing ligands. [ 7 ] It is generally observed that ferromagnetism at room temperature in gold nanoparticles prevails in thiol-stabilized Au nanoparticles. [ 8 ] The crucial electronic event involved on the onset of magnetization in capped gold nanoparticles is a spin symmetry breaking associated with the 5 d and 6 s electrons of the Au atoms involved in the chemical bond with the ligands, which in turn modifi es the relative spin densities at the Fermi energy thus creating a non-zero magnetic moment and a corresponding magnetization.…”
mentioning
confidence: 99%
“…Table 3 discusses some advantages of MNP-based hyperthermia, which have been proved by many studies throughout the past decade. [51,[84][85][86][87][88] It is also shown to be superior over traditional ones. Some of these advantages are discussed next: (I) MNPs have small particle size that can pass through the biological barrier, even to brain; (II) MNPs targeting can be enhanced by specific agents to increase the effectiveness of hyperthermia at targeted site; (III) MNPs not only provide hyperthermia treatment but also can be utilized as a diagnostic agent for MRI; and (IV) it can be heated though alternating magnetic fields.…”
Section: Stimuli-sensitive Drug Deliverymentioning
confidence: 99%
“…SPIONs@Au-LHRH were synthesized as described in our previous publications [18,19]. Briefly, following synthesis of SPIONs of Fe 3 O 4 (average diameter: 5.1 nm) by reduction of Fe(II) acetylacetonate at 210°C using 1,2 hexadecanediol in the presence of surfactants (oleic acid and oleylamine), they were coated with Au in situ through reduction of Au(III) acetylacetonate.…”
Section: Chemicals Cell Culture Supplies and Cellsmentioning
confidence: 99%
“…Based on the Leuschner's study, which showed a practical application of LHRH-SPIONs for targeted delivery, we have reasoned that MNPs bound to LHRH would also serve as ideal candidates for targeted hyperthermia when applied in conjunction with external magnetic fields. Toward realizing this goal, we have previously reported a synthetic strategy to obtain gold-coated SPIONs (SPIONs@Au) and subsequently bound them to LHRH through cysteamine crosslinker [18]. The SPIONs@Au-LHRH thus synthesized were found to have a mean diameter of 6.7 ± 0.8 nm with saturation magnetization (Ms) of 32 emu/g (at 27°C) and a blocking temperature (T B ) of ∼300 K [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation